Phonological System of Muarasipongi Creole - Husnil Hidayat; Jufrizal Jufrizal (Universitas Negeri Padang, 2019)
As a result of language contact, creole is a language phenomena which must be investigated by linguists. This research investigated the phonological system of Muarasipongi creole. The aim of the research was to identify the phonemes and determine the distribution of phonemes. Descriptive-qualitative method was used in conducting the research. Based on the findings, there are 37 phonemes found in Muarasipongi Creole. The phonemes are /p/, /b/, /t/, /d/, /ʧ/, /ʤ/, /k/, /g/, /?/, /h/, /s/, /ʃ/, /m/, /n/, /ŋ/, /ɲ/, /r/, /l/, /w/, /j/. /a/, /i/, /u/, /e/, /o/, /æ/, /ai/, /ua/, /uo/, /ou/, /oi/, /au/, /ei/, /iu/, /ui/, /ae/, and /ia/. In term of phoneme distribution, Muarasipongi creole have variation. The consonants have variation in distribution. Moreover, vowels are complete distribution except phoneme /æ/. Furhermore, none of diphthongs have complete distribution.